Curcumin and tetrahydrocurcumin both prevent osteoarthritis symptoms and decrease the expressions of pro-inflammatory cytokines in estrogen-deficient rats. Issue 1 (December 2016) - Park, Sunmin; Lee, La; Seo, Ji; Kang, Suna
Abstract Background Menopausal symptoms are associated with inflammation. Curcumin is a well-known anti-inflammatory bioactive compound from turmeric whereas tetrahydrocurcumin (THC) is a major metabolite of curcumin that may have different efficacies. However, they have not been studied for anti-menopausal symptoms and anti-osteoarthritis effects. We compared the efficacies of curcumin and THC for preventing postmenopausal and osteoarthritis symptoms in ovariectomized (OVX) obese rats with monoiodoacetate (MIA) injections into the right knee to generate a similar pathology as osteoarthritis. Methods OVX rats were provided a 45 % fat diet containing either (1) 0.4 % curcumin (curcumin), (2) 0.4 % THC, (3) 30 μg/kg body weight 17β-estradiol + 0.4 % dextrin (positive control), (4) 0.4 % dextrin (placebo; control), or (5) 0.4 % dextrin with no MIA injection (normal control) for 4 weeks. At the beginning of the fifth week, OVX rats were given articular injections of MIA or normal-control saline into the right knee and the assigned diets were provided for an additional 3 weeks. Results Curcumin and THC had similar efficacies for skin tail temperature in OVX rats whereas THC, but not curcumin, prevented glucose intolerance, which might be involved in exacerbating osteoarthritis. Both protected against osteoarthritis symptoms and pain-related behaviors better than 17β-estradiol treatment in estrogen-deficient rats. Curcumin and THC prevented the deterioration of articular cartilage compared to control. They also maintained lean body mass and lowered fat mass as much as 17β-estradiol treatment. The improvement in osteoarthritis symptoms was associated with decreased gene expressions of matrix metalloproteinase (MMP )3 andMMP13 and tumor necrosis factor-α, interleukin (IL )1β, andIL6 in the articular cartilage. Conclusions THC and curcumin are effective for treating postmenopausal and osteoarthritis symptoms in OVX rats with MIA-induced osteoarthritis-like symptoms and may have potential as interventions for menopausal and osteoarthritic symptoms in humans.